Resensi Buku: A Body of Praise: Understanding the Role of Our Physical Bodiesin Worship - Shan Bhanuaji (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2026)
This review examines A Body of Praise by W. David O. Taylor, highlighting his central argument that Christian worship must recover the role of the physical body as integral to spiritual formation. Drawing from biblical, historical, and neuroscientific perspectives, Taylor challenges disembodied approaches to liturgy and emphasizes sensory engagement in worship. The book offers a constructive vision of embodied worship that is both theologically grounded and pastorally relevant for contemporary church practice.